2019
DOI: 10.1136/jech-2019-212335
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness as a risk factor for metabolic syndrome: results from the HUNT study

Abstract: ObjectiveMetabolic syndrome (MetS) includes hyperglycaemia, hypertension, central adiposity, elevated triglyceride levels and low levels of high-density lipoprotein cholesterol. All factors are identified as risk factors for cardiovascular disease and mortality. This longitudinal study examined whether loneliness, which has been shown to predict a range of negative health outcomes, increases the risk for MetS.MethodsWe used data from ‘the Nord-Trøndelag Health Study’ (HUNT) which is a large longitudinal health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 40 publications
1
29
1
Order By: Relevance
“…Previous research indicates that loneliness has a reciprocal relationship with depression [26]. Depression is also a possible pathway through which loneliness impacts cardiometabolic health [10], with a large body of evidence suggesting that depressed individuals are more likely to develop type 2 diabetes than those without depression [27]. Given this, we considered depressive symptoms in our analyses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research indicates that loneliness has a reciprocal relationship with depression [26]. Depression is also a possible pathway through which loneliness impacts cardiometabolic health [10], with a large body of evidence suggesting that depressed individuals are more likely to develop type 2 diabetes than those without depression [27]. Given this, we considered depressive symptoms in our analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Loneliness is associated with ageing [ 2 , 3 ] and obesity [ 8 ], both of which are major risk factors for type 2 diabetes [ 9 ]. Further, evidence from large observational cohort studies indicates that loneliness is associated both cross-sectionally [ 8 ] and prospectively [ 10 ] with the metabolic syndrome. However, studies associating loneliness with HbA 1c have been less consistent [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, loneliness has become one of the major public health concerns during the pandemic [2]. Evidence from empirical studies has shown that loneliness is an important risk factor for a myriad of deleterious physical and mental consequences, including early mortality, cardiovascular diseases, metabolic syndrome, suicidal behaviors, depressive symptoms, and cognitive decline [3][4][5][6][7][8][9]. Similarly, during this pandemic, population-based studies have demonstrated significant associations of feelings of loneliness with increased risk of depression, anxiety, psychological distress, poor sleep, alcohol and drug use, and poor quality of life [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…A burgeoning evidence base lends support to these statements, linking loneliness and social isolation to an array of physical and mental health issues. The issues include: depression, anxiety and stress ; poor health behaviours (Hawkley et al, 2009); poor cardiovascular health (Hawkley et al, 2006; poor sleep quality (Kurina et al, 2011;Pressman et al, 2005); more severe common cold symptoms (LeRoy et al, 2017); poor physical health status (Richard et al, 2017); increased risk for metabolic syndrome (Henriksen et al, 2019) and increased risk for mortality (Luo et al, 2012). Overall, this evidence base indicates that loneliness exerts a powerful influence on health.…”
Section: Introductionmentioning
confidence: 99%